Carte de la partie septentrionale du Royaume de Suede avec une table des provinces et villes principales - Chatelain, Henri Abraham (Chatelain, Zacharias, 1690-1754, 1735)
18th century Copper engraving handcolored watercolor. Full color. Relief shown pictorially. Printed across top border: "Carte De La Partie Septentrionale Du Royaume De Suede Avec Une Table Des Provinces Et Villes Principales." Printed in upper right corner: "Tome 4 No. 7." Printed in upper left corner and along left border is a key for all lakes, villages, provinces and rivers categorized by region. Printed in bottom left in border is a key to various places and rivers depicted. Printed in bottom right in border is a key to further places. Printed within center of bottom border are notes describing the geography of Norway, Sweden and Finland: "Remarque Historique: La partie Septentrionale de la Suede eest une des parties de l'Europe qui nous est le moins connue. Les Tables que l'on a places xi dessus et ci a coté serviront a nous en donner une idée generale. On divise le Pais des Lapons en Lapons de Kimi, de Tornea, de Luhlea, de Pithea, d'Uma et d'Angermanie comme on le marquee dans la Carte et dans les Tables ci a cote. Dans les Tables on y distingue les provinces, les Lacs, les Rivieres et les Villes que l'on verra aussi dans la Carte par les renvois alphabetiques." Printed within center of bottom border is a continuation of the historical and geographical notes from the text on the left: "Suite de la Remarque. Qusi que cette Carte ne regarde que la Suede, la Norwegue qui est de la dependence de la Couronne de Danemarck y etant jointe nous a oblige d'en donner une idée abrogee. La Differtation que l'on donnera sur la Laponie et sur tous les pais Septentrionaux apprendra diverses autres particularités que l'on ne pout joindre ici. Outre la description de ces etats on y fait encore remarquer le Golfe de Bothnie et la Bothie Orientale et Occidentale les Villes et les Rivieres les plus remarquables." Depicts part of Norway, Sweden as "Laponie Suedoise," and part of Finland. Divides Sweden into several regions including Kimi, Tornea, Luhlea, D'Angermanie, Pithea and Uhma. Shows the Norwegian Sea and the North Sea as well as the Gulf of Bothnia. Depicts pictorial forests, cities, rivers, lakes and mountains. Henri Abraham Chatelain (1664-1743) was a geographer and publisher. Most of Chatelain's maps were based on the work of Guillaume Delisle. His most famous work was "Atlas Historique" published in 7 volumes from 1705-1720, 1721 and again 1732-1739. The text of this educative atlas was written by Nicholas Gueudville (Johnson). Included in this atlas is one of Chatelain's best known, highly-decorative maps, "Carte trés curieuse de la Mer de Sud…," a large foldout map that displays elaborate cartouches and depicts 75 percent of the globe in longitude. This particular map was published in the later 1735 edition of Chatelain's "Atlas Historique" (Johnson). Source(s): Johnson, W. Vance. "A Farewell to Maps." 28 Oct 1990. Unpublished. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979.